STUDI EKSPERIMEN PENGGUNAAN MIXED ADHESIVE SIKAFLEX-EPOXY PADA KONFIGURASI SAMBUNGAN SINGLE LAP JOINT ALUMINIUM - Widyatno, Alfian; Hastuti, Sri; Nurhadi (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Adhesives are an alternative to many joints because they are cost-effective, corrosion-resistant, neat, and strong for low-load construction such as window/door frames. Aluminum material is rigid but deformable, making it prone to cracks in the adhesive joint area. The addition of sikaflex was chosen because it is a low stiffness and elastic adhesive that bonds well to metals, ceramics, and plastics. The purpose of this research is to analyze the effect of adding sikaflex to epoxy adhesives with a percentage of 15%, 25%, and 35% on the shear tensile strength of aluminum single lap joints. The surface of the adherend was given a roughness treatment by sandblasting method to improve the mechanical interlocking between the adherend and the adhesive.  The sandblasting roughness test before treatment was 0.50 µm to 2.90 µm. Shear tensile test results of sandblasted specimens increased in all mixed adhesive variations. The highest strength mixed adhesive with composition 15%SF: 85%EP. Visual observation showed mixed failure mode between cohesive failure and adhesive failure occurred in all mixed adhesive variations.